FINTECH ADOPTION, FINANCIAL LITERACY, AND MSME SUSTAINABILITY: PERFORMANCE AS MEDIATOR - Utami Setianingrum; Datien Eriska Utami (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study examines the effect of financial technology (Fintech) adoption and financial literacy on the sustainability of Micro, Small, and Medium Enterprises (MSME) with business performance as a mediating variable. The background of this study is based on the strategic role of Msme in the Indonesian economy and the various challenges they face in financial management and digital adoption, where Fintech and financial literacy are considered potential solutions. The research method employs an explanatory quantitative approach, utilizing PLS-SEM analysis techniques. Primary data were collected using questionnaires from 149 MSME actors in Boyolali Regency, Central Java, selected using convenience sampling techniques. The results indicate that financial literacy has a direct positive impact on sustainability and an indirect impact through improved performance. Meanwhile, fintech adoption does not have a significant direct effect on sustainability; its impact is fully mediated through the performance of Msme. In conclusion, this study confirms the role of business performance as a key mediator that transforms technology adoption and financial literacy into sustainable business resilience. The implications of this study highlight the importance of integrated MSME empowerment programs that combine financial literacy improvement with technology adoption assistance, as well as a focus on strengthening operational and financial performance capabilities, laying the foundation for sustainability.